Impact of Selected Corporate Governance Variables on the Financial Performance of Selected Quoted Deposit Money Banks in Nigeria - Eni-Egwu, Catherine Odima; Chimezie James, Madukwe; Beatrice, Ezeilo Chinonye (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This study examined the impact of selected corporate governance variables on the financial performance of selected quoted deposit money bank in Nigeria. More specifically, the study explores the relationship between board size, board composition, audit committee independence, gender diversity, and financial performance - return on equity (ROE) and return on assets (ROA). Arguing from the agency and resource dependency theories, data covering the period 2010-2019 were collected from the audited annual accounts of ten purposively-chosen deposit money banks. To provide robust analysis of data and ensure triangulation of methods, the multiple regression analysis in SPSS version 21 and the Smart PLS structural equation modeling (SEM) were applied. Findings indicate that while board size and audit committee independence are negatively related with corporate financial performance, gender diversity showed positive relationship, and board composition demonstrated mixed relationship. The study recommends among others that firms should try to reduce their board size to plus or minus ten, and also reduce the number of outside (external or non-executive) board members, but with strict adherence to the regulatory guideline. The study proposes a SEM-based model to guide financial institutions post-Covid-19.